Perubahan pH, Al, dan Fe Tanah Sulfat Masam yang Diaplikasi Kompos Limbah Pertanian - Adrianoor Saputra, Riza; Diena, Nurin Nisa Farah; Jumar, Jumar; Irawan, Herri (Faculty of Agriculture Universitas Singaperbangsa Karawang, 2024)
One type of land found in the swamp ecosystem is acid sulfate land. This land has the potential to be developed into agricultural land, especially rice plants. However, it is classified as problematic land because it has negative characteristics and is less fertile. Sulphidic materials are characteristic of acid sulfate soils where pyrite is abundant. The unique properties of pyrite are highly dependent on water conditions and come from marine deposits, namely mineral or organic soils that contain a lot of S which is easily oxidized and have soil acidity that tends to be very low. This research was carried out from June to October 2021 at Sungai Rangas, West Martapura District, Banjar Regency, and the Laboratory of the Department of Soil, Lambung Mangkurat University, Banjarbaru, South Kalimantan. The method used in this study is the design in this study was compiled using a randomized block design (RBD) with a split-plot design. The first factor studied was the type of compost (A) as the main plot consisting of three treatment levels: a1 = rice straw compost, a2 = coffee grounds compost, a3 = oyster mushroom baglog waste compost while the second factor was the dose of compost (B) as a child. The plot consisted of two treatment levels: b1= 0 t ha-1, b2= 20 t ha-1 divided into four experimental blocks so that 24 experimental units were obtained. The results showed that the application of compost waste rice straw, coffee grounds, and baglog of oyster mushrooms at a dose of 20 t ha-1 can increase soil pH and reduce soil soluble Fe and Al-soluble in acid sulfate soils.